O atleta profissional de futebol e o direito do trabalho - Peluso, Fernando Rogério (2009)
The objective of this work is to evidence the main peculiarities and conditions applicable to employment agreements with professional football athletes, specifically in relation to the parties to the agreement, players registration, formal aspects that need to be observed for the entering into of such agreements, working hours, compensation and termination of the agreement. In order to achieve such objective, we will in each respect analyze the general conditions that regulate employment agreements governed by the Restated Employment Laws (Consolidação das Leis do Trabalho) and next we will evaluate how a professional football athlete s employment agreement operates in accordance with the Federal Constitution and the legislation applicable to this type of agreement, as well as the subsidiary application of other rules and laws. We will seek to demonstrate that the football player profession has a number of special conditions that influence the legal analysis of issues resulting from employment agreements and therefore in certain cases cause a legal distancing between employees performing the function of professional football players and employees under the regime of the Restated Employment Laws (Consolidação das Leis do Trabalho)